Assessment of colorectal length using the electromagnetic capsule tracking system: a comparative validation study in healthy subjects. (5th September 2017) - Mark, E. B.; Poulsen, J. L.; Haase, A. M.; Frøkjær, J. B.; Schlageter, V.; Scott, S. M.; Krogh, K.; Drewes, A. M.
Abstract: Aim: We aimed to determine colorectal length with the 3D‐Transit system by describing a 'centreline' of capsule movement and comparing it with known anatomy, as determined by magnetic resonance imaging (MRI). Further, we aimed to test the day‐to‐day variation of colorectal length assessed with the system. Method: The 3D‐Transit system consists of electromagnetic capsules that can be tracked as they traverse the gastrointestinal tract. Twenty‐five healthy subjects were examined with both 3D‐Transit and MRI. Another 21 healthy subjects were examined with 3D‐Transit on two consecutive days. Results: Computation of colorectal length from capsule passage was possible for 60 of the 67 3D‐Transit recordings. The length of the colorectum measured with MRI and 3D‐Transit was 95 (75–153) cm and 99 (77–147) cm, respectively ( P = 0.15). The coefficient of variation (CV) between MRI and 3D‐Transit was 7.8%. Apart from the caecum/ascending colon being 26% ( P = 0.002) shorter on MRI, there were no other differences in total or segmental colorectal lengths between methods (all P > 0.05). The length of the colorectum measured with 3D‐Transit on two consecutive days was 102 (73–119) cm and 103 (75–123) cm ( P = 0.67). The CV between days was 7.3%. Conclusion: The 3D‐Transit system allows accurate and reliable determination of colorectal length compared with MRI‐derived colorectal length and between days. Antegrade or retrograde capsule movement relative to this centreline, as well as the length and speed of movements, may be determined by future studies to allow better classification and treatment in patients with dysmotility.